2019
DOI: 10.1111/mec.15001
|View full text |Cite
|
Sign up to set email alerts
|

The genetic architecture underlying diapause termination in a planktonic crustacean

Abstract: Diapause is a feature of the life cycle of many invertebrates by which unfavourable environmental conditions can be outlived. The seasonal timing of diapause allows organisms to adapt to seasonal changes in habitat suitability and thus is key to their fitness. In the planktonic crustacean Daphnia, various cues can induce the production of diapause stages that are resistant to heat, drought or freezing and contain one to two embryos in developmental arrest. Daphnia is a keystone species of many freshwater ecosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…spider mites 30 ) the photoperiodic clock necessary for termination of diapause is probably not identical to the circadian clock. However, the involvement of cry 2 in diapause termination of Daphnia is likely: In a QTL study, Czypionka et al 31 have identified three isoforms of an ELKS/Rab6 interacting/Cast 396 family member protein (ERC; homologous to the gene bruchpilot ( brp ) in insects) to be potentially involved in diapause termination. Interestingly, brp interacts with the circadian clock although it is not part of the core circadian system 32 .…”
Section: Introductionmentioning
confidence: 99%
“…spider mites 30 ) the photoperiodic clock necessary for termination of diapause is probably not identical to the circadian clock. However, the involvement of cry 2 in diapause termination of Daphnia is likely: In a QTL study, Czypionka et al 31 have identified three isoforms of an ELKS/Rab6 interacting/Cast 396 family member protein (ERC; homologous to the gene bruchpilot ( brp ) in insects) to be potentially involved in diapause termination. Interestingly, brp interacts with the circadian clock although it is not part of the core circadian system 32 .…”
Section: Introductionmentioning
confidence: 99%
“…The evolution of plasticity depends on the strength of selection and the predictability of environmental fluctuations (Leimar et al 2006). To better understand the evolution of adaptive plasticity it is necessary to characterize its genetic background, and this has only been performed in very few studies (Czypionka et al 2018). One open point of discussion on adaptive plasticity considers that either specific loci are responsible for determining a plastic response, or alternatively that loci are co-opted by a number of traits that are adapted to a certain environment (Via et al 1995;Sgrò et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The position of two deleterious, but naturally segregating mutations were mapped [ 8 ]. The same standing QTL panel was later used to map the position of resistance genes to different parasites [ 71 , 116 ] and genes related to sex induction and breaking of diapause [ 5 , 117 ]. The mapping of phenotypes to genotypes has become much easier by the use of next generation sequencing for large number of genotypes, conducting genome wide association studies (GWAS).…”
Section: Experimental Approachesmentioning
confidence: 99%